Soft Law and its Importance in Ensuring Member Statesʼ Compliance with Union Law - Weismann, Paul (Nomos, 2024)
This book is dedicated to the role of soft law in the enforcement of EU law vis-à-vis the Member States. Apart from the Treaty infringement procedure, there is an increasing number of procedures, mostly laid down in secondary law, by which the EU – often availing itself of soft law – aims at ensuring Member States’ compliance with EU law. These procedures are compared with each other, also with respect to their use of soft law, and their conformity with primary law is examined. Diese Arbeit widmet sich der Rolle des soft law bei der Durchsetzung von Unionsrecht gegenüber den Mitgliedstaaten. Neben dem Vertragsverletzungsverfahren gibt es immer mehr, v.a. sekundärrechtlich geregelte Verfahren, mit denen die EU Rechtsdurchsetzung gegenüber den Mitgliedstaaten betreibt, oft auch mittels unverbindlicher Akte. Diese Verfahren werden, auch hinsichtlich der Verwendung von soft law, miteinander verglichen und auf ihre Primärrechtskonformität hin überprüft.